2009
DOI: 10.1007/s00467-008-0980-1
|View full text |Cite
|
Sign up to set email alerts
|

Stunting growth: association of the blood pressure levels and ACE activity in early childhood

Abstract: Angiotensin converting enzyme (ACE) converts angiotensin I to angiotensin II and inactive bradykinin. Several studies carried out in our laboratory have consistently identified three isoforms of ACE, at 65, 90 and 190 kDa, with the 90-kDa isoform being a possible genetic marker of hypertension. Based on these observations and the fact that nutritional stunting can be associated with hypertension, we have investigated the expression and activity of ACE in stunted children and its association with blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
1
6
0
7
Order By: Relevance
“…There was a significant association between the circulating levels of both angiotensin II and ACE activity and systolic BP (SBP, Figure 4). Febba et al [68] recently showed that ACE activity is increased, together with an increase in systolic and diastolic pressure in children with stunting independent of birth weight.…”
Section: Hypertensionmentioning
confidence: 99%
“…There was a significant association between the circulating levels of both angiotensin II and ACE activity and systolic BP (SBP, Figure 4). Febba et al [68] recently showed that ACE activity is increased, together with an increase in systolic and diastolic pressure in children with stunting independent of birth weight.…”
Section: Hypertensionmentioning
confidence: 99%
“…Além disso, na América Latina, encontra-se uma alta prevalência de hipertensão arterial em crianças, adolescentes e adultos com crescimento interrompido por má nutrição (137)(138)(139)(140)(141)(142)(143)(144). Um estudo realizado no Brasil (137), que investigou o comportamento da pressão arterial em uma amostra aleatória de adolescentes com atraso no crescimento (10-16A, n = 56), que vivem em favelas, mostrou um elevado percentual de pessoas com uma pressão acima do percentil 90 e 95, após o ajuste para altura e estavam em maior risco de desenvolver hipertensão.…”
Section: Hipertensão E Diabetes Em Idososunclassified
“…É sabido que na América Latina desnutrição materna e desnutrição infantil são um grande problema a ser resolvido em uma proporção significativa das populações pobres (136). Além disso, na América Latina, encontra-se uma alta prevalência de hipertensão arterial em crianças, adolescentes e adultos com crescimento interrompido por má nutrição (137)(138)(139)(140)(141)(142)(143)(144). Um estudo realizado no Brasil (137), que investigou o comportamento da pressão arterial em uma amostra aleatória de adolescentes com atraso no crescimento (10-16A, n = 56), que vivem em favelas, mostrou um elevado percentual de pessoas com uma pressão acima do percentil 90 e 95, após o ajuste para altura e estavam em maior risco de desenvolver hipertensão.…”
Section: Hipertensão E Diabetes Em Idososunclassified